2019
DOI: 10.1007/s12551-019-00504-7
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical models applied to thyroid cancer

Abstract: Thyroid cancer is the most prevalent endocrine neoplasia in the world. The use of mathematical models on the development of tumors has yielded numerous results in this field and modeling with differential equations is present in many papers on cancer. In order to know the use of mathematical models with differential equations or similar in the study of thyroid cancer, studies since 2006 to date was reviewed. Systems with ordinary or partial differential equations were the means most frequently adopted by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…PDE, unlike ODE, investigates spatial patterns of inherently heterogeneous systems with regionally varying fields. A literature study has revealed the application of these models in various fields, including bone remodeling [ 142 ], dengue [ 143 ] and cancer [ 144 ]. Studies complimented with PDE and ML approaches have also opened a new window for disease treatment [ 145 , 146 ].…”
Section: Future Directionmentioning
confidence: 99%
“…PDE, unlike ODE, investigates spatial patterns of inherently heterogeneous systems with regionally varying fields. A literature study has revealed the application of these models in various fields, including bone remodeling [ 142 ], dengue [ 143 ] and cancer [ 144 ]. Studies complimented with PDE and ML approaches have also opened a new window for disease treatment [ 145 , 146 ].…”
Section: Future Directionmentioning
confidence: 99%
“… 32 In addition, compartmental computer modeling has been used to analyze complex clinical chemistry data, namely, predicting the tumor size based on the analysis of circulating tumor biomarker levels in the plasma of cancer patients. 33 , 34 Another example is the use of a computational pipeline for the diagnosis of common variable immunodeficiency (CVID). This pipeline is based on an automated machine learning approach for diagnosing CVID using flowcytometry to sort the cells.…”
Section: Computational Approaches Used In Analysis Of Clinical Chemismentioning
confidence: 99%
“…Ref. 22 present a review about mathematical models of thyroid cancer, one that discusses different models used and aspects investigated to date. In Ref.…”
Section: Introductionmentioning
confidence: 99%